Pseudomonas fluorescens MFE01 uses 1-undecene as aerial communication molecule - Dupont, Charly A.; Bourigault, Yvann; Osmond, Théo; Nier, Maëva; Barbey, Corinne; Latour, Xavier; Konto-Ghiorghi, Yoan; Verdon, Julien; Merieau, Annabelle (Frontiers in Microbiology, 2023)
Bacterial communication is a fundamental process used to synchronize gene expression and collective behavior among the bacterial population. The most studied bacterial communication system is Quorum Sensing, a cell density system, in which the concentration of inductors increases to a threshold level allowing detection by specific receptors. As a result, bacteria can change their behavior in a coordinated way. While in Pseudomonas quorum sensing based on the synthesis of N-acyl homoserine lactone molecules is well studied, volatile organic compounds, although considered to be communication signals in the rhizosphere, are understudied. The Pseudomonas fluorescens MFE01 strain has a very active Type Six Secretion System that can kill some competitive bacteria. Furthermore, MFE01 emits numerous volatile organic compounds, including 1-undecene, which contributes to the aerial inhibition of Legionella pneumophila growth. Finally, MFE01 appears to be deprived of N-acyl homoserine lactone synthase. The main objective of this study was to explore the role of 1-undecene in the communication of MFE01. We constructed a mutant affected in undA gene encoding the enzyme responsible for 1-undecene synthesis to provide further insight into the role of 1-undecene in MFE01. First, we studied the impacts of this mutation both on Volatile Organic Compounds emission, using Headspace Solid-Phase Microextraction combined with Gas Chromatography-Mass Spectrometry and on L. pneumophila long-range inhibition. Then, we analyzed influence of 1-undecene on MFE01 coordinated phenotypes, including Type Six Secretion System activity and biofilm formation. Next, to test the ability of MFE01 to synthesize N-acyl homoserine lactones in our conditions, we investigated in silico the presence of corresponding genes across the MFE01 genome and we exposed its biofilms to an N-acyl homoserine lactone-degrading enzyme. Finally, we examined the effects of 1-undecene emission on MFE01 biofilm maturation and aerial communication using an original experimental set-up. This study demonstrated that the ΔundA mutant is impaired in biofilm maturation. An exposure of the ΔundA mutant to the Volatile Compounds emitted by MFE01 during the biofilm development restored the biofilm maturation process. These findings indicate that MFE01 uses 1-undecene emission for aerial communication, reporting for the first time this Volatile Organic Compound as bacterial intraspecific communication signal.